1978
DOI: 10.1037/0033-2909.85.4.867
|View full text |Cite
|
Sign up to set email alerts
|

Marital disruption as a stressor: A review and analysis.

Abstract: This article describes some of the major demographic trends in the field of marital disruption and provides an analysis of the evidence linking separation and divorce with a wide variety of physical and emotional disorders. Separation and divorce appear to be profoundly stressful life events. Hypotheses that have been advanced to account for the strong associations between marital disruption and emotional disorder are critically examined. Studies of problems faced by persons undergoing marital disruption and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
221
0
18

Year Published

1982
1982
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 513 publications
(249 citation statements)
references
References 113 publications
7
221
0
18
Order By: Relevance
“…A customer will want to avoid the accompanying psychological and emotional stress and the risk and uncertainty that the termination of the current relationship could bring. 13 Guiltnan 14 identifies four types of switching costs: contractual, set-up, psychological commitment and continuity costs. The author uses Klemperer's 15 contractual costs while in service firms, identifies eight general categories of reason for customers switching: core service failure (26 per cent); failed service encounters (21 per cent); price (17 per cent); response to failed service (11 per cent); inconvenience (10 per cent); competition (4 per cent); ethical problems (4 per cent); and involuntary switching (2 per cent).…”
Section: Introductionmentioning
confidence: 99%
“…A customer will want to avoid the accompanying psychological and emotional stress and the risk and uncertainty that the termination of the current relationship could bring. 13 Guiltnan 14 identifies four types of switching costs: contractual, set-up, psychological commitment and continuity costs. The author uses Klemperer's 15 contractual costs while in service firms, identifies eight general categories of reason for customers switching: core service failure (26 per cent); failed service encounters (21 per cent); price (17 per cent); response to failed service (11 per cent); inconvenience (10 per cent); competition (4 per cent); ethical problems (4 per cent); and involuntary switching (2 per cent).…”
Section: Introductionmentioning
confidence: 99%
“…Каждый следующий брак с еще большей вероятностью так закончится [Brody, Neubaum, Forehand, 1988;Cherlin, 1992]. Благополучные браки обычно оберегают супругов от негативных жизненных ситуаций и стрессов [Waltz, Badura, Pfaff, Schott, 1988], но стресс и нестабильность в браке обладают негативными последствиями для физиологического и эмоционального здоровья супругов [Bloom, Asher, White, 1978] и их детей [Emery, 1982;Grych, Fincham, 1990], а также являются одними из основных причин обращения за консультацией к пси-хологу [Veroff, Kulka, Douvan, 1981] 1 .…”
unclassified
“…Bruce & Kim, 1992;Cartwright, Kravitz, Eastman, & Wood, 1991;Hill & Hilton, 1999;Simon & Marcussen, 1999). This research has consistently shown that couples going through a separation are at greater risk for mental health issues than those who are partnered, or those who have never been partnered (Bloom, Asher & White, 1978;Cairney, Boyle, Offord, & Racine, 2003;Davies, Avison, & McAlpine, 1997;Crago, 1972;Wade & Pevalin, 2004). Such mental health issues include depression (Bruce & Kim, 1992;Richards, Hardy & Wadsworth, 1997),…”
Section: Extant Literature -Separation and Mental Healthmentioning
confidence: 99%